Changing Concepts of Cirrhotic Coagulopathy. (February 2017) - Tripodi, Armando; Primignani, Massimo; Mannucci, Pier M; Caldwell, Stephen H
Abstract : N/A: The state of clinical art of the coagulopathy of cirrhosis changed considerably over the last decade. Until 2005, cirrhosis was considered as the epitome of the hemorrhagic coagulopathies and the abnormal hemostasis tests associated with the disease were corrected with infusion of fresh frozen plasma or platelets to minimize the risk of bleeding. Since that time, a great deal of work has been done and there is now a change of paradigm. The prothrombin time once considered as an isolated measure of bleeding risk was rejected, and cirrhosis shifted from a purely hemorrhagic construct to a mixed and thrombosis‐prone paradigm. In this article we examine the interesting history of how these conceptual changes came about.